(untitled) (Olhar de Professor, 2022)
The article analyzes the trajectory of the National Curricular Common Base (BNCC) that spanned two different government cycles: Dilma Rousseff (2011-2016) and Michel Temer (2016-2018). Documents such as BNCC versions, ordinances and guidelines were analyzed. Publications dealing with the process of building this policy were also consulted. Two contexts guided the analysis: conjunctures and policy contentes. The analysis brought some evidence: BNCC’s trajectory does not reveal linearity; Political scenarios, in a way, are translated into official texts, as there are significant differences between the 2016 and 2017 versions in relation, for example, to the guiding principles, the actors involved in the construction and the target audience of this policy. Finally, official texts are important to understand the trajectory of a policy, because, in addition to revealing advances and ruptures, they provide elements to understand the complexity that permeates the process of formulation and implementation of educational policies.